A series of dysprosium-based hydrogen-bonded organic frameworks (Dy–HOFs): thermally triggered off → on conversion of a single-ion magnet. Issue 10 (13th September 2019) - Wang, Hai-Ling; Ma, Xiong-Feng; Zhu, Zhong-Hong; Zhang, Yi-Quan; Zou, Hua-Hong; Liang, Fu-Pei
Abstract : A series of dysprosium-based HOFs (Dy–HOFs) were designed and synthesized for the first time under solvothermal conditions. Herein, we achieved the magnetic off → on SIM switching of Dy–HOFs under thermal driving conditions. Abstract : The discovery of hydrogen-bonded organic frameworks (HOFs) has offered new opportunities for the expansion of porous materials. The field of HOFs has also introduced a new challenge—the design and synthesis of lanthanide HOFs (Ln–HOFs). Given that Ln complexes have various coordination modes, complex coordination structures, and irregular shapes, Ln–HOFs are extremely difficult to construct. In this study, a series of dysprosium-based HOFs (Dy–HOFs), namely, [Dy(L 1 )3 (CH3 OH)·Phen] n (Cl-1 ) and [Dy(L 2 )3 (CH3 OH)·Phen] n (Br-1 ), were designed and synthesized for the first time under solvothermal conditions of 5, 7-dichloro/dibromo-2-methyl-8-quinolinol (L 1 /L 2 ), Dy(NO3 )3 ·6H2 O, and 2, 9-dimethyl-1, 10-phenanthroline (Phen). The porous Cl-1 (Br-1 ) was filled with Phen molecules linked by various supramolecular weak interactions. After Cl-1 (Br-1 ) was incubated at 260 °C for 2 h under a N2 atmosphere, we found that only free Phen in the pores disappeared and Cl-2 (Br-2 ) was obtained. Magnetic characterization studies revealed that Cl-1 and Br-1 exhibited inconspicuous slow relaxation behavior. Unexpectedly, Cl-2 and Br-2 exhibited an evident single-ion magnetic (SIM) behavior, and their energy barriers were 97 and 87 K, respectively. We achieved the off → on SIM conversion of the Dy–HOFs for the first time.